MECHANISM STUDY OF MADEIRA VEIN (ANREDERA CORDIFOLIA (TEN). V. STEENIS) LEAVES AS ANTIHYPERTENSIVE AGENT - Nuryanti Garmana, Afrillia
Hypertension is the cardiovascular disease that the third leading cause of death in Indonesia with a prevalence of 26.5%. Pharmacological treatment of hypertension by using antihypertensive drugs is a long term therapy, hence there is a risk of adverse effect. Natural source can be explored to find a safer drug which has antihypertensive effect, one of the sources is madeira vein. Madeira vein has many benefits including treatment kidney damage, diabetes, stroke, hemorrhoids, fever, abdominal pain, inflammation, antimicrobial, and improving blood circulation. Madeira vein is also one of the recommended plants for lowering blood pressure. This study aims to determine the mechanism of binahong leaves extract and its active fraction, determine marker compound in the active fraction. Antihypertensive effect of ethanolic extract of madeira vein leaf (EEMV) were performed by testing diuretic and saluretic effects as well as antihypertensive effect testing in adrenaline-induced hypertensive animal model. The extract was fractionated and yielded three fractions, namely n-hexane fraction (HF), ethyl acetate fraction (EF), and water fraction (WF). On the extract and fractions, antihypertensive effect was examined in dexamethasone-induced hypertensive animal model. Further studies of antihypertensive mechanisms were carried out by testing the increasement level of nitric oxide (NO) in vivo; alpha blockers activity, vasodilation effect through NO pathways, and calcium channel blocker activity ex vivo; and also angiotensin converting enzyme inhibition activity in vitro. Determination of marker compound was done by thin layer chromatography (TLC) by comparing fraction profile with standard compound. In the examination of diuretic, saluretric and antihypertensive effects in adrenaline-induced animal models, EEMV 50, 100, and 200 mg/kg bw were used. The diuretic effect was performed using the modified Lipschitz method. EEMV 200 mg/kg bw showed significantly different diuretic effect compare to negative control group in 24 hours observation, whereas saluretic effect occurred at 50 mg/kg bw. Increasement of sodium ion excretion was not followed by increasement potassium ion. In the adrenaline-induced animal model, heart rate was measured by ADInstrument® Non-Invasive Blood Pressure (NIBP) controller. EEMV 50 mg/kg bw decreased heart rate caused by adrenaline injection significantly compared to positive control (p<0.05). In the examination of antihypertensive effects in dexamethasone-induced animal model, EEMV 100 mg/kg bw; HF 0.02 mg/kg bw; EF 1.66 mg/kg bw; and WF 40.73 mg/kg bw were used. The rat’s blood pressure was measured by CODA® tail-cuff blood pressure system. Hypertensive rat model was occured on day 7 after administration of dexamethasone injection. EEMV, EF, and WF could significantly reduce systolic blood pressure (SBP) at day 14 (7 days of treatment) (p<0.05) with decreasement of SBP were 26.8; 34.1; and 40.5 mmHg, respectively. Diastolic blood pressure (DBP) began to decrease from day 8 (1 day treatment) in the EEMV group with DBP reduction of 24.1 mmHg. In the HF, EF, and WF groups, decreasement of DBP occurred on day 14 (7 days of treatment) with decreasement 22.0; 24.5; and 35.4 mmHg, respectively. NO level was measured using uv-visible spectrophotometry at wavelength of 546 nm after serum sample was reacted with a Griess reagent. The absorbance value was linear with NO content which was calculated through linear regression equation of calibration curve of sodium nitrite standard. NO level in rat’s serum was significantly increased at 90 minutes after administration of EEMV 100 mg/kg bw and WF 40.73 mg/kg bw, respectively, 48.5 and 36.36 ?M. administration of EF only increase NO level 19.89 ?M. In the ex vivo experiment, rabbit aortic rings were exposed to EEMV 1.57 mg/mL; HF 0.0003 mg/mL; EF 0.03 mg/mL; and WF 0.64 mg/mL. The respond of aortic rings to EEMV, HF, EF, and WF were observed in the kymograph, then percentage of relaxation and relaxation time were calculated from the graph obtained. In norepinephrine-induced contraction, EEMV, HF, EF, and WF showed percentage of relaxation 60.9; 39.2; 48.2; and 52.5%, respectively. Relaxation time of all groups were significantly decrease compared to norepinephrine group (p<0.05). In norepinephrine-induced contraction with methylene blue pretreatment, the percent of relaxation were 21.4; 30.7; 21.6; and 23.8%, respectively for EEMV, HF, EF, and WF, and there was no reduction in relaxation time. In KCl-induced contraction, the percentage of relaxation of EEMV, HF, EF, and WF were 42.2; 20.4; 49.1; and 35.8%, respectively, but no reduction in relaxation time. ACE inhibitor activity test was performed using Hip-His-Leu as the substrate and measured the formed product using uv- visible spectrophotometry at wavelength 228 nm. From the absorbance data, percentage of enzyme inhibition was calculated and IC50 value was determined. IC50 of EEMV, HF, EF, and WF were 20.76, 198.13, 115.77, and 88.41 ?g/mL, respectively. The TLC profile showed that ursolic acid could be a marker compound in HF, apigetrin could be a compound marker in EF, while in WF marker compound was a flavonoid compound. Based on the experiments, EEMV was proved preclinically had antihypertensive effects with mechanism of action(s) as diuretic and saluretic, adrenergic receptor blocker, vasodilator through NO pathway (in vivo and ex vivo), calcium channel blocker, and also inhibitor ACE. The major mechanisms are vasodilator through NO pathway and beta-1 receptor antagonist. Water fraction showed antihypertensive effect by vasodilation through NO pathway (ex vivo and in vitro) and ACE inhibition but not through calcium channel blockade. Ethyl acetate fraction showed vasodilation through NO pathway (ex vivo), ACE inhibition, and calcium channel blockade. N-hexane fraction showed vasodilation through NO pathway (ex vivo).